Gesellschaftsrecht - Grunewald, Barbara (Mohr Siebeck, 2020)
This textbook offers a current, systematic and complete presentation of company law in Germany. This new edition has been completely revised and updated.Different conditions apply to libraries for this title; please contact the sales department.
PublicationDate: 20201022
Keywords: Allgemeines -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht